Properties and Potential Application of Lead-Free (BaZr0.2Ti0.8O3) and Lead-Based (PbZr0.52Ti0.48O3) Flexible Thick Films - Jelena Bobić; Nikola Ilić; Željko Despotović; Adis Džunuzović; Robertas Grigalaitis; Ivan Stijepović; Biljana Stojanović; Mirjana Vijatović Petrović (Crystals, 2023)
For the last several decades, energy harvesters based on piezoelectricity from mechanical vibration have emerged as very promising devices that are being explored extensively for their functionality in energy technologies. In this paper, a series of flexible lead-free BaZr0.2Ti0.8O3 (BZT)/PVDF and lead-based PbZr0.52Ti0.48O3 (PZT)/PVDF piezocomposites with variable filler content up to 50 vol% were prepared by a hot pressing method. The structure and morphology of the BZT and PZT powders, as well as the distribution of the piezo-active filler in the obtained flexible films were characterized by XRD and SEM analysis. In addition, the remnant polarization (Pr) and leakage current were also investigated to evaluate the breakdown strength in both types of flexible films. The calculations of storage energies and output voltage obtained for the investigated materials revealed an increasing trend with an increasing amount of BZT and PZT active phases. The maximum storage energy of 0.42 J/cm3 (and energy efficiency of 40.7 %) was obtained for the PZT–PVDF (40–60) films, while the maximum output voltage of about 10 V (~10 μA) was obtained for the PZT–PVDF (50–50) flexible film. In addition, a comparison between the properties of the lead-based and lead-free flexible films, as well as the potential use of these films as energy storage and energy harvesting systems were analyzed.